Causes of Caries and Preventive Measures - Asrorovna, Kholboyeva Nasiba; Sadikovich, Mavlonov Azamat; Davronovich, Arabov Abduvokhid (American Journal of Bioscience and Clinical Integrity, 2025)
Caries is the decay of tooth tissue caused by bacteria living in the oral cavity. The pathology occurs due to improper or insufficient oral hygiene. If caries is not treated, it causes severe pain and can completely destroy the tooth.